Twitter for Public Organization: Communication and Public Engagement in the Generation Unlimited Initiative - Pertiwi, Nandariza Yoga; Purwanti, Nurul Dwi (JURNAL KOMUNIKASI INDONESIA, 2023)
The United Nation Children’s Fund has programs and initiatives involving various stakeholders and the active participation of audiences worldwide, so communication becomes a crucial aspect of the organization's operations especially in increasing public involvement. This study aims to identify the role of opinion leader UNICEF—especially the initiation of Generation Unlimited—through message types in its communication process on Twitter to increase public engagement using a mix-method design through big data analytics and content analysis. Locus of the study is the opinion leader’s Twitter account, which interacts with the Generation Unlmited account. 4,095 tweets are collected and accessed via Twitter Application Programming Interface using Python. According to the findings, the opinion leader with the highest popularity is @Unilever, and the message type with the highest engagement is the interactive one from @UNICEFROSA. Opinion leader with the highest popularity value does not necessarily have messages with the highest engagement value either. The primary contribution of this article is to provide the finding about certain types of opinion leaders and content types that impact increasing public engagement. We believe the research can inspire other public organizations to develop and optimize their communication engagement through their social media platform.